The Prophets Agree : The Function of the Book of the Twelve Prophets in Acts - White, Aaron W., (Biblical Interpretation Series ;, 2020)
How Luke uses and interprets Scripture continues to captivate many. In his new work The Prophets Agree, a title inspired by James' words at the Jerusalem Council, Aaron W. White turns over one rock that has remained unturned. Interpretation of the four quotations of the Minor Prophets in Acts frequently isolates each citation from the other. However, this full-length study of the place of the Minor Prophets in Acts asks what difference it makes to regard these four quotations as a singular contribution to Acts from a unified source. By an in-depth study of each quotation, an innovative method of intertextuality, and an eye to the overall agenda of Acts, White proves the importance of reading the Twelve Prophets in unity when it is quoted in Acts, and the integral role it plays in the redemptive-historical plot line of Acts.